A Single-Center, Cross-Sectional Study of Children with Steroid-Resistant Nephrotic Syndrome in Southern China (Iranian Journal of Kidney Diseases, 2021)
Introduction. We conducted a cross-sectional study on children with steroid-resistant nephrotic syndrome (SRNS) in a single center in Southern China. Methods. A total of 166 SRNS cases in the Paediatric Nephrology Center of the First Affiliated Hospital of Sun Yat-Sen University from September 1, 2006, to August 31, 2016 were retrospectively analysed. The inclusion criteria were: 1) age ≤ 14 years, 2) diagnosed with SRNS, and 3) without purpura nephritis, immunoglobulin A nephropathy, lupus nephritis, or another secondary nephritis. Incidences of primary/ late steroid-resistance and curative effects were analysed. Results. The median follow-up time was 4.64 (2.64 to 8.11) years. There were 67 cases of complete remission (CR) (40.36%), 46 cases of partial remission (PR) (27.71%), 31 cases of no remission (NR) (18.67%), 18 cases of end-stage renal disease (ESRD, 10.84%, including 7 cases of kidney transplantation), and 4 cases of death due to hematoma and severe infection after renal biopsy; renal failure after progression to ESRD; sepsis during glucocorticoid (GC) + Cyclosporine A (CsA) treatment; and multiple organ failure at the onset of disease, respectively. For the 8 cases with gene mutation, unnecessary drug treatment should be reduced due to their low responsiveness to immunosuppressive treatment. Female, patients with hematuria, primary steroid-resistance (PSR) type and histopathologic focal segmental glomerulosclerosis (FSGS) were more likely to have higher ESRD rate. Subgroup analysis of ESRD suggested that female patients and patients with PSR type were more likely to develop ESRD. Cox-regression analysis showed that female (HR = 3.04, 95% CI: 1.18 to 7.86; P < .05), without hematuria (HR = 0.36, 95% CI: 0.14 to 0.91; P < .05), and LSR type (HR = 0.17, 95% CI: 0.04 to 0.74; P < .05) were significantly associated with ESRD. Kaplan-Meier survival analysis also showed the same trends. Conclusion. Of the 166 SRNS cases, 68.07% of patients achieved CR or PR, 18.67% of cases had NR, 10.84% of cases developed ESRD, and 2.41% of patients died during follow-up. Female gender, hematuria, and PSR type were positively associated with ESRD.